Double‐blind randomized trial on the efficacy of the Gufoni maneuver for treatment of lateral canal BPPV. (4th February 2013) - Mandalà, Marco; Pepponi, Emanuela; Santoro, Giovanni Paolo; Cambi, Jacopo; Casani, Augusto; Faralli, Mario; Giannoni, Beatrice; Gufoni, Mauro; Marcelli, Vincenzo; Trabalzini, Franco; Vannucchi, Paolo; Nuti, Daniele
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis The need for class I and II studies on the efficacy of liberatory maneuvers in the treatment of lateral canal benign paroxysmal positional vertigo (LC‐BPPV) motivated the present double‐blind randomized trial on the short‐term efficacy of the Gufoni liberatory maneuver (GLM). Study Design Double‐blind randomized controlled trial. Methods Seventy‐two patients with unilateral LC‐BPPV were recruited for a multicentric study. Patients were randomly assigned to treatment by GLM (n = 37) or sham treatment (n = 35). Subjects were followed up twice (at 1 hour and 24 hours) with the supine roll test by blinded examiners. Results At 1‐ and 24‐hour follow‐up, 75.7% and 83.8% of patients, respectively, undergoing GLM had recovered from vertigo, compared to around 10% of patients undergoing the sham maneuver (P < 0.0001). Conclusion To the best of our knowledge, this is the first class I study on the efficacy of the GLM in the treatment of LC‐BPPV in both geotropic and apogeotropic forms. GLM proved highly effective compared to the sham maneuver (P < 0.0001). The present class I study of the efficacy of the GLM changes the level of recommendation of the method for treating LC‐BPPV from level U to level B for the geotropic variant and from level B to level A for the apogeotropic variant of LC‐BPPV. Level of Evidence 1b. Laryngoscope, 2013